Duality of the matrix transpose and matrix conjugate inverse maps - Granario, Daryl Q. (Animo Repository, 2022)
Choi (1973) established a duality between the inversion and ad- junction of bounded invertible Hilbert space operators, giving analo- gies between the similarity and congruence relations. We discuss Choi’s results in the finite-dimensional setting and show that a similar duality can be found between another pair of maps, the matrix transpose and the matrix conjugate-inverse maps.